UJI SIFAT FISIK DAN IRITASI EKSTRAK ETANOL BUAH RUKEM (Flacourtia rukam) DALAM SEDIAAN SUNSCREEN BASIS GEL - Neneng Rachmalia Izzatul Mukhlishah; Dwi Monika Ningrum (Pharmaceutical and Traditional Medicine, 2020)
Rukem fruit (Flacourtia rukam) with anthocyanin active compound has been widely studied and is known to be efficacious as an antioxidant, and further research related to its formulation continues to be carried out. The formula developed in this study was a sunscreen preparation on a gel basis with a gelling agent Carbopol 940. This study aimed to determine the physical properties and irritation power of a sunscreen extract of rukem extract on a gel base. Sunscreen gel is made by the smelting method with the concentration of Rukem Fruit Ethanol Extract 3% (F1), 6% (F2) and 9% (F3). The gels from the three formulas were then evaluated for their physical properties, including dispersion, adhesion and pH. Also evaluated also the irritative nature of the skin by using human test subjects, namely irritation testing for four hours (human 4-hour patch test) (Botham et al, 1998). Experimental data obtained were then analyzed statistically with a confidence level of 95%. Statistical test results with LSD test showed that there were significant differences between formulas. The higher the concentration of ethanol extract of rukem fruit, the greater the spread and adhesion (p <0.05). However, the pH test after the Kruskal Wallis test for each formula did not provide a significant difference (p> 0.05). Human 4-hour patch test irritation test results also showed that the sunscreen gel of Rukem ethanol extract with extract concentrations of 3%, 6% and 9% did not cause irritation effects